2014
DOI: 10.1515/jpem-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Common approach to childhood obesity in Japan

Abstract: Although the prevalence of childhood obesity is plateauing, it remains a social concern. The Japan Society for the Study of Obesity devised criteria for obesity disease as a morbid state that requires medical treatment in 2002. Moreover, the Japanese Ministry of Health, Labour and Welfare announced diagnostic criteria for childhood metabolic syndrome in 2010 because of the increasing number of children with lifestyle-related diseases. The treatment of obesity needs to be prioritized, and three principles, othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
2
22
0
1
Order By: Relevance
“…Although MetS occurs less often in children, several studies have established a prevalence of MetS in approximately 3.0%-4.0% of children and adolescents [7][8][9] . These phenomena have been reported in Japanese children [10][11][12] . Furthermore, in previous cross-sectional studies, the risk for MetS has been reported to be associated with fatness and aerobic fitness in European 13) , American 14) , Canadian 15) , Australian 16) , and Asian children [17][18][19] .…”
Section: Introductionsupporting
confidence: 61%
“…Although MetS occurs less often in children, several studies have established a prevalence of MetS in approximately 3.0%-4.0% of children and adolescents [7][8][9] . These phenomena have been reported in Japanese children [10][11][12] . Furthermore, in previous cross-sectional studies, the risk for MetS has been reported to be associated with fatness and aerobic fitness in European 13) , American 14) , Canadian 15) , Australian 16) , and Asian children [17][18][19] .…”
Section: Introductionsupporting
confidence: 61%
“…The most common cause of obesity in children is a positive energy balance due to caloric intake higher than caloric expenditure combined with a genetic predisposition for weight gain ( 1 ). While the rate of increase in the overall prevalence of childhood obesity in the developed world has slowed or plateaued ( 2 , 3 , 4 ), the most severe and recalcitrant form of obesity has increased progressively ( 5 ). In the United States in 1999–2004, almost 4% of children and adolescents of 2–19 yr of age were classified as severely obese, and as recently as 2011–2012, the prevalence of severe obesity increased to approximately 6% in this age group ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, obesity and overweight are highly prevalent risk factors for a number of chronic conditions, including diabetes, CVD and cancer ( 1 ) Despite its lower incidence in Japan (as compared with other countries), obesity still raises public-health concerns here, especially towards male adults, children and adolescents ( 2 , 3 ) . Therefore, there has been much interest in exploring possible determinants of weight gain.…”
mentioning
confidence: 99%